Wind-Conditioned 20th Century Decline of Birch Treeline Vegetation in the Swedish Scandes - Kullman, Leif (ARCTIC, 2010)
The study focused on a frequent, although not dominant, mode of treeline change in the Swedish Scandes over the past century. Monitoring of stand density decline in a wind-exposed subalpine birch (Betula pubescens ssp. tortuosa) population was carried out over the past 30 years. The overall result included substantial and unbalanced individual mortality and a drastic reduction in stature of surviving birches. Radiocarbon dating of in situ subfossil birch-tree remains in an adjoining but windier site revealed complete stand demise over the past century or so. It is inferred that the extant and extinct birch populations represent different phases in an unbroken process of stand-level demise, hypothetically initiated in response to reindeer disturbance during the final phase of the Little Ice Age. This process was subsequently communicated more or less autogenically in a leeward direction as a consequence of the exposed and drought-prone nature of the site. Increasing westerly wind circulation and decreasing soil moisture (earlier snowmelt) during the past century may have contributed in this respect, although these aspects require further study. Within strongly wind-exposed terrain, a century of substantial warming has not sufficed to offset the birch decline. The results highlight the conclusion that under certain circumstances, wind and associated ecological and physiological effects are the overriding determinants of treeline position and structure. These are fundamental insights for generating realistic landscape-scale models of treeline change in a hypothetically warmer future. Cette étude porte sur un mode fréquent, bien que non dominant, de changement de la limite des arbres dans les Scandes suédoises au cours du siècle précédent. Durant les 30 dernières années, on a suivi le déclin dans la densité d’un peuplement de bouleaux pubescents subalpins (Betula pubescens ssp. tortuosa) qui étaient exposés au vent. Le résultat global comprenait une importante mortalité individuelle non compensée ainsi qu’une ...